MENINGKATKAN KEMANDIRIAN BELAJAR MELALUI KONSELING BEHAVIOR DENGAN TEKNIK COGNITIVE RESTRUCTURING - Ika Nur Zulaikha; Aldila Fitri Radite Nur Maynawati; Awik Hidayati (JCOSE Jurnal Bimbingan dan Konseling, 2022)
Self-regulated learning has not been possessed by many students and is a problem that is often ignored. So that special attention and handling are needed from educators, as well as counselors to help deal with students who have low learning independence. Tirtomoyo. This study uses the Classroom Action Research (CAR) method with a quantitative approach. The subjects of this study were 10 students of class X Accounting 1 SMK Sultan Agung Tirtomoyo who were taken using purposive sampling technique. This research was conducted in 2 cycles with 2 meetings. Data collection techniques through observation, interviews, and documentation. Data analysis used descriptive statistics with the percentage correction formula. The success indicator of this research is if the average percentage reaches 75%. The results of pre-cycle observations showed that students' self-regulated learning was still categorized as low with an average value of 48.8%. After the action in the first cycle, there was an increase with an average value of 71.5%. Furthermore, the action in the second cycle the average value becomes 86.3%, so that it has reached the specified success indicator. Based on this, it can be concluded that through the application of behavioral counseling with cognitive restructuring techniques, it can increase the self-regulated learning of students in class X Accounting 1 SMK Sultan Agung Tirtomoyo.